2017
DOI: 10.1002/chem.201701906
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Functionalization of Polysaccharides—Towards Biocompatible Hydrogels for Biomedical Applications

Abstract: Hydrogels have emerged as a highly interdisciplinary topic as they play a significant role for a vast number of applications. They have been studied extensively as materials for contact lenses, wound dressing and as filler material in soft-tissue augmentation, in which classical polymer backbones such as hydroxyethylmethacrylate (HEMA) are typically employed. More recently, polysaccharides have received attention, particularly in the fields of regenerative medicine and tissue engineering, as ideal candidate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 65 publications
0
49
0
1
Order By: Relevance
“…With the assistance of droplet microfluidics, multicomponent reactions, typically the Passerini three-component (P-3CR), and the Ugi four-component reaction (U-4CR), can be applied to produce microgels with a rather uniform size [70,71]. Unlike the regular methods of microgel formation, where the hydrogel building blocks need to be premodified to introduce certain functions, multicomponent reactions can simply introduce and extend functions by changing one block to another in a library-like fashion [72,73]. As an example, Hauck et al [70] reported the single-step synthesis of micro-sized polysaccharide based multifunctional gels through multicomponent reactions, in particular P-3CR and U-4CR.…”
Section: Fabrication Techniques For Three-dimensional (3d) Cell Micromentioning
confidence: 99%
“…With the assistance of droplet microfluidics, multicomponent reactions, typically the Passerini three-component (P-3CR), and the Ugi four-component reaction (U-4CR), can be applied to produce microgels with a rather uniform size [70,71]. Unlike the regular methods of microgel formation, where the hydrogel building blocks need to be premodified to introduce certain functions, multicomponent reactions can simply introduce and extend functions by changing one block to another in a library-like fashion [72,73]. As an example, Hauck et al [70] reported the single-step synthesis of micro-sized polysaccharide based multifunctional gels through multicomponent reactions, in particular P-3CR and U-4CR.…”
Section: Fabrication Techniques For Three-dimensional (3d) Cell Micromentioning
confidence: 99%
“…On the other hand, as the branching proportion increases, the solubility progressively decreases, and those dextrans possessing more than 43% of α-(1→3) are considered to be water insoluble [86]. In any case, the relatively high water solubility of dextrans, as well as their high stability in both mild acidic and basic conditions and its large amount of hydroxylic groups, make dextrans an excellent material for undertaking different derivatization protocols or any kind of chemical or physical crosslinking [86,87]. Generally, the C-2 hydroxyl group is the most reactive, and the conjugation of different molecules to dextran can be carried out following different procedures [86], as depicted in Figure 2.…”
Section: Dextranmentioning
confidence: 99%
“…Hydrogel‐based wound healing is claimed as one of the most effective methods for wound treatment. The interface between hydrogels and wound bed plays a significant role in the rapid wound healing, which provide a biocompatible platform, adequate moisture, and the ability to isolate bacteria . Tissue engineering is a regenerative technique including in vitro reconstruction of organisms and the transplant of these organisms to the site where tissue needs to be regenerated in vivo, requiring the construction of artificial cellular scaffolds that mimic extracellular matrix .…”
Section: Introductionmentioning
confidence: 99%